The Impact of Preoperative Nutritional Status on the Survival of Patients With Esophageal Squamous Cell Carcinoma - Chen, Shao-bin; Liu, Di-tian; Chen, Yu-ping (Frontiers in Surgery, 2021)
Background: The goal of this study was to investigate the impact of different nutritional parameters in patients with esophageal squamous cell carcinoma (ESCC) who underwent surgical resection. Methods: A total of 620 patients with ESCC who underwent esophagectomy were analyzed. A receiver operating characteristic curve was constructed to set the appropriate cutoff points for five nutritional parameters: serum albumin (SA), body mass index (BMI), geriatric nutritional risk index (GNRI), prognostic nutritional index (PNI), and a new modified nutritional risk index (mNRI). Survival analyses were performed to calculate overall survival and investigate the independent prognostic factors. Results: The median preoperative BMI, SA, GNRI, PNI, and mNRI values were 20.90, 42.75, 102.95, 51.90, and 63.90, respectively. The corresponding optimal cutoff points were 18.75 for BMI, 43.05 for SA, 98.5 for GNRI, 51.45 for PNI, and 61.45 for mNRI. All nutritional parameters were significantly correlated with tumor length and pT category. Decreased nutritional parameters were significantly correlated with poor survival in univariate analysis; however, only the mNRI was an independent prognostic factor in multivariate analysis (P=0.041). Conclusions: Nutritional parameters are convenient and valuable prognostic factors in ESCC patients who undergo surgical resection. The new mNRI parameter may be superior to the other nutritional parameters.